Transformation of healthcare with information technologies - Duplaga, Mariusz; Zieliński, Krzysztof; Ingram, David (Studies in health technology and informatics, 2004)
The accession of new EU member states demands considerable effort on their part, aimed at developing common policies and strategies. This book reports on the results of cooperation between researchers and centres representing both new EU entrants and those countries, that have been part of the Community for a long time.